Research in using Polyurethane Foam to Mitigate Rock Bolt Installation Difficulties. Issue 52 (December 2018) - George, Benjamin; Pierson, Lawrence; Barrows, Richard
Rock bolts are commonly used on transportation projects to stabilize cut slopes, reinforce undermined or unsupported blocks, and reduce potential for large rock slides. Installing bolts can be challenging. Locations where bolts are useful may not be easily accessible for personnel or large equipment, and targeted blocks generally are marginally stable. In addition, jointed rock with openings and voids, which are typical conditions, complicate hole advancement and full grout encapsulation. These issues can lead to construction delays, claims, reduced corrosion protection, or shorter design life. This paper describes research conducted to address two rock bolting challenges in open-jointed rock: i) advancement of drill holes to design depth, and ii) successful completion of grouting through the application of injected polyurethane foam (PUF). Testing utilized double-stacked concrete blocks aligned in rows to simulate a rock mass with vertical fractures. Steel spacers were placed between the stacks to simulate 2-, 4-, 6-, and 8-inch apertures. A standard rock drill advanced holes using a 3-inch bit. Research showed PUF could: bridge simulated aperture sizes up to 8 inches, survive drilling action during secondary reaming, resist drilling air and grouting pressures, and reduce grout consumption.